The air dose rate around the Fukushima Dai-ichi Nuclear Power Plant: its spatial characteristics and temporal changes until December 2012 - Mikami, Satoshi; Maeyama, Takeshi; Hoshide, Yoshifumi; Sakamoto, Ryuichi; Sato, Shoji; Okuda, Naotoshi; Sato, Tetsuro; Takemiya, Hiroshi; Saito, Kimiaki (Journal of environmental radioactivity, 2015)
Distribution maps of air dose rates around the Fukushima Dai-ichi Nuclear Power Plant were constructed using the results of measurement obtained from approximately 6500 locations (at most) per measurement period. The measurements were conducted 1 m above the ground using survey meters in flat and spatially open locations. Spatial distribution and temporal change of the air dose rate in the area were revealed by examining the resultant distribution maps. The observed reduction rate of the air dose rate over the 18 months between June 2011 and December 2012 was greater than that calculated from radioactive decay of radiocesium by 10% in relative percentage except decontaminated sites. This 10% difference in the reduction of the air dose rate can be explained by the mobility of radiocesium in the depth direction. In the region where the air dose rate was lower than 0.25 μSv h−1 on June 2011, the reduction of the air dose rate was observed to be smaller than that of the other dose rate regions, and it was in fact smaller than the reduction rate caused by radioactive decay alone. In contrast, the reduction rate was larger in regions with higher air dose rates. In flat and spatially open locations, no significant difference in the reduction tendency of air dose rates was observed among different land use classifications (rice fields, farmland, forests, and building sites). [Display omitted] •Dose rate distribution maps were created from the measurements at 6500 locations.•Dose rate spatial distributions and temporal changes over 18 months were revealed.•No notable difference in reduction rate among different land use types was seen.•Different temporal changes were observed depending on the initial 2011 dose rate.